2020
DOI: 10.2147/lra.s272410
|View full text |Cite
|
Sign up to set email alerts
|

<p>Postoperative Thoracic Epidural Analgesia: Adverse Events from a Single-Center Series of 3126 Patients</p>

Abstract: Purpose Thoracic epidural analgesia (TEA) has been shown to reduce postsurgical morbidity and mortality; nevertheless, major and minor complications can occur. We report our 10-year experience with TEA and incidence of complications. Patients and Methods Patients received continuous infusion TEA (0.2% ropivacaine and 2 µg ml −1 fentanyl) to control postoperative pain. Every 8 hours, the acute pain service recorded the analgesia regimen and occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 33 publications
(28 reference statements)
3
18
0
Order By: Relevance
“…Previous studies have reported disconnection rates in the range of 1.7-2.3% [4,19,20]; these rates were comparable with the rate in this study's old group, which was 1.9%. In the clinical study, there was a signi cant difference in disconnection rates among the groups; speci cally, these rates were highest in the new group and lowest in the taping group.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Previous studies have reported disconnection rates in the range of 1.7-2.3% [4,19,20]; these rates were comparable with the rate in this study's old group, which was 1.9%. In the clinical study, there was a signi cant difference in disconnection rates among the groups; speci cally, these rates were highest in the new group and lowest in the taping group.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have reported dislodgement rates in the range of 1.2-5.1% [4,19,20]. The present rates were comparable with or lower than those previously reported, suggesting that this approach may be bene cial.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…S. aureus is one of the most frequent pathogens as its isolation was reported in more than half of epidural abscesses. 14 Gram-negative bacteria accounted for about 15–20%. 4 , 6 , 15 , 16 In our case, the organism isolated from both blood and purulent cultures was S. aureus .…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic epidural analgesia (TEA) has long been considered as the preferred technique of analgesia after thoracic surgery as it reduces postoperative pain after video-assisted thoracoscopic surgery (VATS) or thoracotomy, and reduces postoperative ileus [ 6 , 7 , 8 , 9 ]. However, epidural analgesia induces a sympathetic block that can cause intra- and postoperative hypotension and acute urinary retention, and catheter placement can lead to neurological damage in rare cases [ 10 , 11 ]. Thus, various other RA techniques have been developed and assessed in thoracic surgery, such as the paravertebral block, the erector spinae plane block (ESP), and intrathecal analgesia (IA) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%